WTO Rulings and the Veil of Anonymity. (4th August 2022) - Pauwelyn, Joost; Pelc, Krzysztof
Abstract: Despite a general push for greater transparency, opacity continues to play an important function in international tribunals. The World Trade Organization (WTO) is a case in point. While it has done much to increase its openness, the very design of its dispute settlement body is premised on anonymity in some essential respects. We examine two such instances, each dealing with the authorship of dispute rulings. First, we use text analysis tools to demonstrate that the WTO's panel reports appear to be largely drafted by WTO Secretariat staff rather than the panellists themselves. This appears especially true for the WTO's most systemically important disputes. Second, we show that the formal anonymity of dissenting opinions, which is required by the WTO's rules, is a thin veil. Using the most recent Appellate Body's dissent for demonstration, we use text analysis to pinpoint its likely author. In both these instances, we argue that anonymity exists by design: it serves to strike a balance between judicial autonomy and political control. Yet, in both settings, due to increased scrutiny and widespread access to text analysis tools, the equilibrium relying on anonymity is likely to be upset, with implications for the institution's future design. We argue that the ultimate result may be a beneficial one and offer a menu of reform options.